Nervonic acid level in cerebrospinal fluid is a candidate biomarker for depressive and manic symptoms: A pilot study. Issue 4 (18th February 2021) - Kageyama, Yuki; Deguchi, Yasuhiko; Hattori, Kotaro; Yoshida, Sumiko; Goto, Yu‐ichi; Inoue, Koki; Kato, Tadafumi
Abstract: Objective: Our previous metabolomics study showed that the plasma nervonic acid levels were higher in patients with major depressive disorder (MDD) than those in healthy controls and patients with bipolar disorder (BD). To examine whether the nervonic acid levels differ in the central nervous system, we investigated the levels in the cerebrospinal fluid (CSF) of patients with MDD, BD, and healthy controls. Methods: Nervonic acid levels in CSF were measured by gas chromatography time‐of‐flight mass spectrometry. The participants included 30 patients with MDD, 30 patients with BD, and 30 healthy controls. Results: In contrast to our previous study, no significant differences were found in the nervonic acid level in the CSF among the patients with MDD, BD, and the healthy controls. Though no significant state‐dependent changes were found among the three groups, we did observe a significant negative correlation between the nervonic acid levels and depressive symptoms in the depressive state of patients with MDD and BD (r = −0.38, p = .046). Further, a significant positive correlation was found between the nervonic acid levels and manic symptoms in the manic state of patients with BD (r = 0.79, p = .031). Conclusion: The nervonic acid levels in the CSF did not differ among the patients with MDD, BD, and the healthy controls; however, a significant negative correlation with depressive symptoms and a positive correlation with manic symptoms was observed. Thus, the nervonic acid levels in the CSF may be a candidate biomarker for mood symptoms. Abstract : The cerebrospinal fluid (CSF) nervonic acid levels were not different among major depressive disorder patients (MDD), bipolar disorder patients (BD), and healthy controls.CSF nervonic acid levels had significant negative correlation with depressive symptom in MDD and BD, and positive correlation with manic symptom in BD.Further study is needed to understand the biological meaning of CSF nervonic acid level in MDD and BD.